What Brexit means for EU and UK social policy - Hantrais, Linda (Bristol, 2019)
"Drawing on a range of disciplinary, conceptual and theoretical approaches, this book analyses the complex interconnections between social policy formation and implementation in the European Union before and during the UK’s membership. It explores the issues, debates and policy challenges facing the EU at different stages in its development, and shows how the UK promoted and hampered social integration. With the UK’s decision to leave the EU as one of the greatest challenges in the EU’s history, this book seeks to understand the role played by social policy in the referendum campaign and withdrawal negotiations, and considers what Brexit means for social policy development both in the UK and across the EU."